Studies on the behaviour of peridomestic and endophagic M form Anopheles gambiae from a rice growing area of Ghana. - Charlwood, J.D.; Tomás, E.V.; salgueiro, P.; Egyir-Yawson, A.; Pitts, R.J.; PintoJ (Bulletin of Entomological Research, 2011)
The 'paddy paradox', the occurrence of large populations of vectors but low amounts of malaria transmission where irrigated rice is grown, was investigated in a village in Ghana where M form Anopheles gambiae are common. Peridomestic and indoor host-seeking mosquitoes were collected in tent traps and light traps over 21 consecutive nights at the start of the rainy season in June 2009 when the population increased exponentially from less than 100 per night to over 1000. Infection rates in the overall mosquito population were 0.3% and in the estimated parous population were 1.9%. Numbers of An. gambiae in the tent trap peaked between midnight and 02:40 am. The majority of insects were taking their first blood meal, as virgins or shortly after mating. More than expected were collected in the light trap during a rainstorm at the start of the rains but overall numbers were not affected. Fewer than expected were collected after a subsequent storm. Recruitment to the adult population decreased over the following days. It is hypothesised that the 'paddy paradox' is due to young pre-gravid insects dispersing more widely than gravid ones, not necessarily to low survival in the mosquito.